Respuesta :
the answer is 14 you just have to substitute x with the given number and finish the equation
Answer:
(f – g)(2) = 12.
Step-by-step explanation:
Given : f(x) = 3x²+1 and g(x) =1-x .
To find : which expression is equivalent to (f – g)(2).
Solution : We have given f(x) = 3x²+1 and g(x) = 1-x .
(f – g)(2) = f (2 ) - g(2) .
g(x) = 1-x .
Plug x = 2 .
g(2) = 1 - 2 .
g(2) = - 1.
For f(x) =3x²+1
Plug x = 2
f( 2) =3 (2)²+1.
f(2) = 12 + 1.
f(2) = 13 .
Then , (f – g)(2) = f (2 ) - g(2) .
Plugging the values
(f – g)(2) = -1 + 13
(f – g)(2) = 12
(f – g)(2) = 12.
Therefore, (f – g)(2) = 12.